P38 Evaluation of response shift in those with chronic ankle instability following a 4-week comprehensive intervention - Powden, CP; Hoch, JM; Jamali, BE; Hoch, MC (British journal of sports medicine, 2017)
Study DesignInterrupted time-series.ObjectiveTo examine if individuals with chronic ankle instability (CAI) experience a response shift (RS) in self-reported function following a 4 week rehabilitation program.BackgroundEvaluation of self-reported function is important during the rehabilitation process. RS may confound the assessment of self-reported function.Methods and MeasuresTwenty adults (15 females; age=24.4±7.0 years; height=169.29±10.1 cm; weight=70.6±12.9 kg) with self-reported CAI participated. Inclusion criteria included ≥1 previous ankle sprain,≥2 episodes of giving way in the previous three months, and ≤24 on the Cumberland Ankle Instability Tool. Subjects participated in 12 intervention sessions that included balance training, ankle strengthening, and talocrural joint mobilizations over 4 weeks. Subjects also completed daily home ankle strengthening and gastroc-soleus complex stretching. Patient-reported outcomes (PRO) were assessed before the intervention (pre-intervention), 24–48 hours following intervention cessation (post-intervention), and 2 weeks following intervention cessation (follow-up). At post-intervention and follow-up, participants completed retrospective evaluations of their baseline function (then-test-post-intervention, then-test-follow-up) to assess RS. PROs included the Foot and Ankle Ability Measure (FAAM) ADL, FAAM-Sport, modified Disablement of the Physically Active scale (mDPA), and Fear-Avoidance Belief Questionnaire (FABQ). One-way ANOVAs evaluated the presence of RS (pre-intervention, then-test-post-intervention, then-test-follow-up). Two-way ANOVAs examined differences in RS adjusted change (then-test-post-intervention – post-intervention; then-test-follow-up – follow-up) and traditional change (pre-intervention – post-intervention; pre-intervention – follow-up). Alpha was set a-priori at p≤0.05.ResultsRS was not identified for any PRO, p>0.124 (FAAM-ADL: pre-intervention=88.63%±8.07%, then-test-post-intervention=86.79%±9.66%, then-test-follow-up=86.37%±9.90%; FAAM-Sport: pre-intervention=80.16%±10.20%, then-test-post-intervention=77.97%±13.47%, then-test-follow-up=76.41%±12.88%; mDPA-Physical: pre-intervention=13.25±7.75, then-test-post-intervention=14.80±8.63, then-test-follow-up=16.45±8.44; FABQ-Physical: pre-intervention=12.6±4.22, then-test-post-intervention=11.5±5.22, then-test-follow-up=10.80±5.31). Greater RS adjusted change was only identified for the FAAM-ADL (p=0.032). A significant time main effect for the mDPA-Physical (p=0.032) indicated greater change at follow-up regardless of change type. No other significant results were identified (p>0.070).ConclusionRS did not occur in individuals with CAI following conservative rehabilitation. Traditional assessment of self-reported function is accurate for evaluating the short-term effects of rehabilitation.